Independent regulatory authorities: analysing accountability, responsibility and transparency - Tripathi, Sudhanshu (2018)
A regulatory authority is an autonomous body established by a federal, state or provincial government with a view to serve the interests of all stakeholders in a society. As the modern state is passing through neo-liberal phase towards reforming public services for accomplishing its goals for good governance, the role of Independent Regulatory Authorities becomes very important. But the spread of independent regulators means that more and more aspects of our lives are shaped by decisions made by institutions that are neither popularly elected nor are they under direct control of elected officials. Obviously, this has important implications for their accountability, responsibility and transparency in the present age of expanding democracy. A way-out may be to re-theorise public authority as an office for coordinating and harmonising diverse interests in a professional way so as to suit the requirements of governance conjointly performed by the state, civil society and market. - Reproduced.
Keywords: Accountability; Transparency